An Analysis of the Physics Textbook Content Within the Next Generation Science Standards (NGSS) - Alahmad , Nidhalأحمد; Albaqami, Maha (Jordan Journal of Educational Sciences, 2017)
This study aimed to analyze the physics textbooks in Saudi Arabia in light of the Next Generation Science Standards (NGSS). The descriptive analytical method was used in this study. Also, the physics books analysis tool had been prepared in accordance to the next generation physics science standards and in the energy dimension for the following three essentials: (Disciplinary core ideas, the science and engineering practices and the crosscutting concepts). The following results had been reached. The three essentials in the physics curriculum books in high schools of Saudi Arabia had applied the standards by (33.33 %), which was a low percentage and was shown in three chapters of the first term of physics curriculum of grade ten. Also, the disciplinary core ideas was the most present essential in the physics curriculum by a medium level (51.9 %) . While in the second place was the crosscutting concepts (interrelated) by a low application percentage (31.1 %). The science and engineering practices came in the last place by a very low percentage (16.35 %). There was variation in the level of applying the main standard for each essential, thus “conservation of energy and energy transfer” was the most present standard but was applied in the content by a very low rate ( 22.2%). On the other hand, “constructing explanations and designing solutions” was the least present standard in the physics curriculum, which was present by only (0.3 %).